Calling for a Reappraisal of the Impact of Quinoa Expansion on Agricultural Sustainability in the Andean Highlands [Llamado a Una Revaluación del Impacto de la Expansión del Cultivo de Quinua Sobre la Sostenibilidad Agrícola en el Altiplano Andino] - Saez-Tonacca, L; Peredo-Parada, S (Universidad de Tarapaca, 2014)
The debate on the environmental and social sustentainability of quinoa in its area of major world production (southern highlands of Bolivia) revived with the acceptance by the United Nations of the Bolivian proposal to declare in 2013 as the Year of the Quinoa. Public debate focused on local impacts of quinoa expansion in the Southern highlands of Bolivia, denouncing several negative impacts of quinoa culture such as land degradation, socioeconomic disrupts and biodiversity loss. However, the global or at least the international implications of the expanding quinoa market were less debated and often in caricature, varying between culpability and ingenuity among consumers, while Andean producers were described as trapped by poverty or short sighted greed. If researchers are to make a relevant contribution to the debate on the impact of quinoa expansion on the social and environmental sustainability of the Andean agriculture, is it necessary to re-evaluate present knowledge and ignorance about local Andean production systems integrated with links at the global scales, taking into account local- global interactions. In the present paper are revisited some major ill- founded assertions commonly expressed in this debate and three lines of arguments are used to support the need for a more cautious and ethical approach to quinoa related issues. © 2014, Universidad de Tarapaca. All rights reserved.